Helping Teachers Visualize Students' Performance - Paiva, Ranilson; Bittencourt, Ig Ibert; Lemos, Wansel (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
The growth in the number of online courses evidences a new paradigm where education is available anywhere and anytime (and, hopefully, to any person). In this new paradigm, courses occur in online learning environments, which rely on information and communication technology to promote learning and teaching. However, researchers report that, on average, 85% of students drop out these courses, and they blame the lack of teacher's support. In this regard, it is necessary to help teachers analyze the data these environments generate, extracting relevant information to guide their decisions. Learning Analytics, Educational Data Mining and Data Visualization can be used to deal with these data, but training teachers on these techniques would demand them time and effort, and the effectiveness is unknown. We propose, instead, the use of Data Viz to help teachers aggregate and "see" their students according to their performance level. We asked teachers to interact with some visualizations. We then checked if they understood the information presented, and asked about their perceptions regarding the: utility, ease of use, attitude towards use, intention to use, aesthetics, the color scheme used and the vocabulary used. The results indicate teachers understood and had positive perceptions regarding the visualizations used.